The impact of safety communication on machinery injuries among farmers - Leppälä, Jarkko; Nysand, Matts; Ronkainen, Ari; Suokannas, Antti; Rautiainen, Risto (Vytautas Magnus University, 2024)
This study examined agricultural machine accidents in Finland. In Finland, the relative share of the number of machine accidents of all accidents in agriculture has grown. In addition, agricultural machinery causes more than half of farmers' deaths at work. Most of the machine accidents occur when using field machinery. The two main objectives of the study were 1) to reduce farmers' machine accidents and their costs by publishing machine safety information cards in a magazine for farmers, and 2) to evaluate the impact of this safety information on the occurrence of machine accidents by following up accident statistics. In 2017, ten information cards on agricultural machinery safety were published in the Koneviesti farm machinery magazine. The topics of the information cards were the most dangerous farm machinery and how to avoid accidents with these: tractors, seeding and tilling machines, automatic functions in field machinery, trailers, ATVs, combines, front loaders, machinery used in livestock production, personal protective equipment, and machine maintenance work. One year after the intervention, the statistics of accidents caused by these machines were analysed, from ten years before to one year after the intervention. A statistically significant decrease in accident development after the intervention was observed among Koneviesti's farmer subscribers. By contrast, no corresponding decrease in accident development was observed among other farmers who were not subscribers to the Koneviesti magazine. The study produced practical training material on agricultural machinery safety.
Keywords: farm safety; agriculture; machine injury; accidents; safety communication